Continuous delivery of code : key to exploiting opportunities - Humble, Jez ([Place of publication not identified] : O'Reilly, 2015)
"There was a time when businesses could only reap the opportunities that strong market signals yielded. Businesses moved slowly and couldn't gamble resources on anything but the strongest opportunities--the cost was too high. But now, by focusing on speed and scale, you can respond rapidly to weak signals in the market to exploit opportunities or quickly decide against them. Join Jez Humble in this free webcast as he shows how continuous delivery of code is the key to exploring and exploiting opportunities in an inexpensive and scalable way. He'll present real-world examples and give you concrete guidelines for reducing cost and risk in your organization while powering innovation at the same time."--Resource description page.
Presenter, Jez Humble.
Title from title screen (viewed April 29, 2016).
Date of publication from resource description page.
Keywords: Computer software -- Development -- Management; Computer software -- Quality control; Computer software -- Management; Logiciels -- Qualité -- Contrôle.; Logiciels -- Gestion; Computer software -- Development -- Management; Computer software -- Management; Computer software -- Quality control; Electronic videos